Functional Approach for the Development and Production of Novel Extreme Biocatalysts - Blamey-Alegria, J (American Chemical Society, 2019)
There is a growing interest in replacing chemical catalysts used in several industrial processes with more efficient and environmentally friendly alternatives. To this end, enzymes represent highly efficient biocatalysts that allow for a decrease in overall production costs and environmental pollution. However, one of the biggest challenges to overcome in successfully using biocatalysts instead of chemical catalysts is to find stable and active biocompounds at the various harsh conditions at which industrial processes usually take place. Microorganisms living in extreme environments have proven to be a valuable source of highly efficient and stable biomolecules. These special types of biocatalysts have adapted to withstand extreme conditions, producing low amounts of by-products under a wide range of conditions, and thus are of paramount importance in industrial applications. A good strategy to finding new enzymes as potential biocatalysts is the functional approach. This approach seeks the discovery of extremophiles and their enzymes in extreme environments that display similar conditions to the industrial process in which the biocatalysts are required. After the desired enzyme is obtained, a recombinant version of the enzyme is produced in order to avoid the low biomass and protein yields when working with native enzymes from extremophiles. To obtain enough biomass for protein purifications and downstream analyses, the process must be optimized and scaled up, using quality control points to produce efficient and reproducible enzyme products. This functional approach has been successfully used to develop enzyme products for the market. © 2019 American Chemical Society.